EFFECTIVENESS OF SURGICAL TECHNIQUE OF LARYNX MANIPULATION IN CASES OF PUBERPHONIA - Khan, Muhammad Ahmed; Khan, Muhammad; Ahmed, Attique; Usman, Hasan Bin (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the effectiveness of surgical technique of laryngeal manipulation to manage cases of puberphonia (mutational falsetto). Methodology: Total 18 patients fulfilling the inclusion criteria were selected from ENT outpatient department of CMH Bahawalpur and Mardan. All the cases underwent laryngeal manipulation under general anesthesia. In the procedure, both vocal cords were crushed with the help of laryngeal forceps with mild force and larynx was stretched anteriorly with the help of blade of macintoch laryngoscope by placing it in the vallecule. Postoperative effectiveness was assessed two weeks and one month after the procedure. The procedure was termed effective when the voice of affected case changed from high pitched to post-pubescent low pitched variety. Results: Age of the patients ranged from 15 to 23 years (mean 17.56 ±2.20). Out of 18 patients, 15 cases showed improvement in voice after one month; the effectiveness of this surgical technique in treating puberphonia was 83.33%. Rest of 03 cases failed to show desired improvement in voice and they were sent for speech therapy and psychological assessment. Conclusion: The surgical technique of direct laryngoscopic larynx manipulation was found effective in treating cases of puberphonia (mutational falsetto) in majority of patients.